Ogłoszenia sprzedaży odzieży damskiej a metody wpływania na odbiorcę - Karwowski, Stanisław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
The article is devoted to a linguistic analysis of sale advertisements for women’s clothing. The main purpose of the article is to identify the means used by the authors of advertisements for women’s clothing in order to encourage the customers to make purchase. The study concentrates on the linguistic and visual aspects of the discussed microtexts. Firstly, the conducted studies have showed that the authors of advertisements try to establish dialog with an addressee of their message by the use of question forms or imperative mode. Secondly, a macroact which is the advertisement of clothing, can be composed of at least nine microacts that are intended to encourage, praise, advise or promise. In order to achieve this, the advertisers use statements, abuse exclamations, emoticons, create messages that are informatively worthless. Thirdly, the authors of advertisements attach great attention to the aspect of credibility of the message, and because of that often direct attention to well-known persons, institutions or the terms of warranty. The conducted study has demonstrated that language is a basic and most important tool in constructing effective advertising messages.